Freqüência de irrigação no cultivo hidropônico da alface - Luz, Gean Lopes da (2008)
The objective of the work was to verify the influence of four intervals between the irrigations on the production of lettuce in hydroponics system and the retention of nutrient solution, besides more determining the best interval between irrigation at each time of cultivation. The experiments were carried out at four times during one year, in the nutrient film technique (NFT), inside a polyethylene greenhouse. The experimental designer was randomized complete blocks in a factorial scheme 4x4, consisted of four intervals between irrigations (T15 - 15 min of irrigation at intervals of 15 min; T30 - 15 min of irrigation at intervals of 30 min; T45 - 15 min of irrigation at intervals of 45 min and T60 - 15 min of 60 irrigation at intervals of min) and four times of cultivation (spring, summer, autumn and winter). Had been determined the temperature and the incident global radiation inside of the greenhouse, as well as the electric energy consumption in each treatment. There were no interaction between times of cultivation and irrigation regimes for the variables dry biomass of leaves (FMSF), of steam (FMSC), of roots (FMSR) and total (FMST), leaf area index (IAF), volume of the roots (VR) and retention of nutrient solution in the roots (RET). There were significant differences among intervals between irrigations just for FMSR and VR. To times of cultivation there were significant differences for all the variables, which are attributed to the distinct meteorological conditions of each time. The FMSF and IAF were not reduced by the magnification of the interval between irrigation since 15 up to 60 min. The FMSR and the VR enlarged with the magnification of the interval between irrigation, causing retention of the nutritional solution. This retention allowed the magnification of the interval between irrigation without the incidence of water deficit. In all the times of cultivation, the T60 treatment was adjusted, showing a decrease of 53.57% in electric consumption compared to T15, without reduction in productivity.